University-school cooperation: perspectives of pre-service teachers, practice teachers and faculty members / Sultan Selen Kula and Mutlu Pınar Demirci Güler - Kula, Sultan Selen; Demirci Güler, Mutlu Pınar (Universiti Teknologi MARA, 2021)
The research aimed to determine the views and expectations of pre-service teachers studying in the field of classroom teaching, practice teachers in practice schools, and faculty members responsible for courses related to teaching practice regarding teaching practice processes. The research was designed as a case study from qualitative research designs. The study group consists of 36 female and 9 male, aged between 21 and 25, totally of 45 pre-service teachers; 16 female and 30 male, aged between 30 and 51, totally of 46 practice teachers; 4 female and 7 male, aged between 30 and 51, totally of 11 faculty members. The data was collected in writing with separate forms for pre-service teachers, practice teachers, and faculty members. The data was analyzed by thematic analysis. The results of the research suggest that the existing operation regarding the university-school collaboration is insufficient and those pre-service teachers have the expectation to increase the practice courses in terms of number and duration. It is thought that the interaction between the university and the school should be improved in all aspects. This research is expected to be a guide for revealing expectations of related parties and improving the process during the teaching practice.